The role of innovation and entrepreneurship employee training programs in enhancing organizational commitment from the perspective of industry–education integration - Zijing Wu; Qiang Li; Biao Zhang (Frontiers in Psychology)
This study aims to explore the role of employee training programs in enhancing organizational commitment. In the context where organizational commitment is crucial for enterprises’ stable development and employee training programs are an important part of human resources development, understanding their relationship is of great significance. Qualitative research methods were employed. Specifically, semi - structured interviews were carried out with employees from diverse industries. Then, thematic analysis was used to analyze the interview data. Through the thematic analysis, several key themes emerged. The relevance of training content to employees’ job roles and career aspirations has a significant impact on training effectiveness. Employees highly value practical and work - applicable training, which is closely linked to job satisfaction. The quality of trainers is also crucial, as competent and engaging trainers can enhance the perceived value of training. Moreover, knowledge sharing promoted by training programs benefits employees’ personal and professional development and strengthens the organization’s collaborative culture. The results highlight that these findings have practical implications for managers. They should design training programs that match employees’ needs and career goals, invest in improving trainers’ capabilities, and create a knowledge - sharing - friendly environment. By taking these actions, managers can enhance employees’ job satisfaction, skills, and career growth, thereby strengthening organizational commitment. Looking ahead, future research could conduct longitudinal studies to track the long - term effects of training on organizational commitment. Also, exploring the influence of organizational culture and individual differences on training outcomes can offer more targeted training strategies for different organizations and employees.